2020
DOI: 10.31234/osf.io/bmt4s
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Narratives bridge the divide between distant events in episodic memory

Abstract: Many studies suggest that information about past experience, or episodic memory, is divided into discrete units called “events.” Paradoxically, we can often remember experiences that span multiple events. Events that occur in close succession might simply be bridged because of their proximity to one another, but many events occur farther apart in time. Intuitively, some kind of organizing principle should enable these temporally-distant events to become bridged in memory. We tested the hypothesis that episodic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(26 citation statements)
references
References 58 publications
(101 reference statements)
2
24
0
Order By: Relevance
“…If so, then boundary-evoked voxel patterns should exhibit higher encoding-retrieval similarity for Coherent Narratives than for Unrelated Narratives. Furthermore, in line with our previous behavioral work (Cohn-Sheehy et al, 2020), we hypothesized that this kind of reinstatement would predict the number of details recalled about Coherent Narrative events.…”
Section: Introductionsupporting
confidence: 53%
See 4 more Smart Citations
“…If so, then boundary-evoked voxel patterns should exhibit higher encoding-retrieval similarity for Coherent Narratives than for Unrelated Narratives. Furthermore, in line with our previous behavioral work (Cohn-Sheehy et al, 2020), we hypothesized that this kind of reinstatement would predict the number of details recalled about Coherent Narrative events.…”
Section: Introductionsupporting
confidence: 53%
“…Our next analyses focused on recall of CN and UN events. In a previous behavioral study, we found that, across three experiments, participants were able to recall more details about CN than UN events (Cohn-Sheehy et al, 2020). In the present study, the number of details recalled from CN events (mean=10.71 details per cue, SD=9.4, max=41.5) was numerically higher than recall of details from UN events (mean=8.65 details per cue, SD=9.1, max=40.0), though this effect did not meet the threshold for statistical significance (t(24) =1.98, p=.059, Cohen's d=0.22).…”
Section: Recall Of Coherent Narrative Events Scales With Reinstatemenmentioning
confidence: 78%
See 3 more Smart Citations